Interaction of avian adenovirus with the immune system of poultry - NANDI, S; RAY, J P; SARKAR, P; MAITI, N K (The Indian Journal of Animal Sciences, 2013)
The role of an avian adeno virus (AAV) as an immunosuppressive agent was investigated in 2-week-old broiler chicks. The immunosuppressive effect on humoral and cellular immune responses was assessed by response of infected chicks to unrelated antigens and 1-chloro-2-4 dinitrobenzene (DNCB) respectively. The virus adversely affected the immune system of infected birds as decreased immunological responses was observed as compared to control. The histopathological examination of bursa of Fabricius and thymus revealed focal area of necrosis and lymphocyte depletion. Viral antigen was detected in the faecal samples at 7 days postinfection(pI) and peak excretion of antigen reached at 14 days PI.